On‐Site Testosterone Biosensing for Doping Detection: Electrochemical Immunosensing via Functionalized Magnetic Nanoparticles and Screen‐Printed Electrodes. Issue 47 (14th December 2020) - Sanli, Serdar; Moulahoum, Hichem; Ghorbanizamani, Faezeh; Gumus, Zinar Pinar; Timur, Suna
Abstract: Point‐of‐care approaches are in constant need of novel and highly performant portable devices. Doping is a constant issue seen in the athletic field, and a need for mobile and trustable methods for detection are highly sought. The current work proposes a portable biosensor based on a screen‐printed electrode (SPE) and functionalized magnetic particles for testosterone detection. The functionalized magnetic particles were characterized with SEM and the designed biosensor was analyzed amperometrically (Pulse Voltammetry (DPV), Cyclic Voltammetry (CV), and Electrochemical Impedance Spectrometry (EIS)). Results demonstrate linearity between 50–1000 ng/mL with a LOD of 23.68 ng/mL. Q‐TOF/MS method was performed to compare with the biosensor over serum and urine. Furthermore, the selectivity of the biosensor was tested in the presence of various interferents. The designed biosensor shows good potential in doping detection and prevention of illicit use due to the versatility of application that it covers. Abstract : A highly sensitive and efficient portable sensor for testosterone based on functionalized magnetic nanoparticles. The platform demonstrates a LOD of 23.68 ng/mL with a range between 50–1000 ng/mL. The sensor is highly selective and offers a great advantage due to simplicity and reusability that can be applied in multiple biomedical and athletic fields.